The Learning Implementation of Writing Non-Literary Text by Online during the Covid-19 Pandemic in the Eighth Grade Students at State of Junior High School of 8 Yogyakarta - Eva Kurniawati; Teguh Setiawan (Universitas Teuku Umar, 2021)
AbstractThis study aims to describe the planning and implementation of learning to write non-literary texts online during the Covid-19 pandemic, the barriers in the implementation of learning, and the efforts of teachers to overcome these barriers. This research is a qualitative descriptive study. The subjects of this study were teachers and the eighth grade students in state of Junior High School of 8 Yogyakarta. The object of research is focused on planning and implementing learning to write non-literary texts, barriers, and the efforts of teachers to overcome barriers to learning online during the Covid-19 pandemic. Data obtained by observation, interview, and documentation techniques. Data analysis techniques include the stages of data reduction, data presentation, and conclusions. Based on the research conducted, it can be seen that learning planning includes syllabus and specific lesson plans for online learning, while the implementation of learning includes objectives, teaching materials, methods, media, and evaluation. Furthermore, the barriers faced by teachers include facilities and infrastructure, signal stability, and online learning design creativity. On the other hand, the barriers faced by students include signal stability, data packages, and the learning process. The teacher has a role in overcoming the barriers to online learning that occur. Keywordswriting; non-literary text; online learning